Olive pomace-derived pectin limits lipid droplet hypertrophy and collagen deposition and is associated with hepatic transcriptional changes in a MASLD murine model - Luna Barrera-Chamorro; Jose L. del-Rio-Vazquez; Africa Fernandez-Prior; Elvira Marquez-Paradas; Carmen M. Claro-Cala; Teresa Gonzalez-de la Rosa; Maria Torrecillas-Lopez; Sergio Montserrat de la Paz (Food Bioscience, 2026)

Shrimp (sub-)national traceability and retail fraud detection using stable isotopes and multi-element profiling - V. Deklerck; R.P. Davis; A. Rodriguez-Zunino; S. Khongtanakrittakorn; S. Hofem; J. Jungkeit; A. Leyton; M. Osorto-Nuñez; C. Podmore; L. Prior; C.C. Smith; B. Soule; et al. (Food Control, 2026)

Proceedings from Nourish Now: A science dialogue on improving adolescent health through nutrition - Mario G. Ferruzzi; Regan L. Bailey; Teresa A. Davis; Heather J. Leidy; Jamie I. Baum; Jill Castle; Angela De Leon; Eva C. Diaz; Victor L. Fulgoni; Carolyn Gunther; Leslie Kaplan; Bracha Kopstick; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Advances in virus detection using carbon and quantum dot technologies: a review - Ana L. Silva; Marcela A. Segundo; João A.V. Prior (Analytica Chimica Acta, 2026)

Minimizing use of nonhuman primates to inform risk to fertility and of adverse pregnancy outcomes with pharmaceuticals - Christopher J. Bowman; Ann Baker; Diann L. Blanset; Kimberly C. Brannen; Gary J. Chellman; Brian Enright; Wendy Halpern; Bethany R. Hannas; Kazushige Maki; Fumito Mikashima; Shermaine Mitchell-Ryan; Eve Mylchreest; et al. (Regulatory Toxicology and Pharmacology, 2026)

Physiological and behavioural plasticity improves resilience to chronic hypoxia and warming in a dryland river fish - Zoe A. Ross; Jonathan Marshall; Andrea Prior; Craig E. Franklin; Matthew Hipsey; Rebecca L. Cramp (Science of The Total Environment, 2025)

What is ‘good evidence’ for environmental decision making? Insights from professionals working at the science-policy interface - Elizabeth A. Nyboer; Andrew N. Kadykalo; Nathan Young; Vivian M. Nguyen; Trina Rytwinski; John-Francis Lane; Joseph R. Bennett; Nathan Harron; Susan M. Aitken; Graeme Auld; David Browne; Aerin L. Jacob; et al. (Environmental Science & Policy, 2025)

European Network for Optimization of Veterinary Antimicrobial Therapy (ENOVAT) guidelines for antimicrobial use in canine acute diarrhoea - L.R. Jessen; M. Werner; D. Singleton; C. Prior; F. Foroutan; A.A. Ferran; C. Arenas; C. R. Bjørnvad; E. Lavy; F. Allerton; K. Allensbach; L. Guardabassi; et al. (The Veterinary Journal, 2024)

Efficacy of antimicrobial and nutraceutical treatment for canine acute diarrhoea: A systematic review and meta-analysis for European Network for Optimization of Antimicrobial Therapy (ENOVAT) guidelines - K. Scahill; L.R. Jessen; C. Prior; D. Singleton; F. Foroutan; A.A. Ferran; C. Arenas; C.R. Bjørnvad; E. Lavy; F. Allerton; J.S. Weese; K. Allenspach; et al. (The Veterinary Journal, 2024)

Delimiting the cryptic diversity and host preferences of Sycophila parasitoid wasps associated with oak galls using phylogenomic data - Yuanmeng M. Zhang; Sofia I. Sheikh; Anna K. G. Ward; Andrew A. Forbes; Kirsten M. Prior; Graham N. Stone; Michael W. Gates; Scott P. Egan; Linyi Zhang; Charles Davis; Kelly L. Weinersmith; George Melika; et al. (Molecular Ecology, 2022)
Cryptic species diversity is a major challenge regarding the species‐rich community of parasitoids attacking oak gall wasps due to a high degree of sexual dimorphism, morphological plasticity, small size and poorly known biology. As such, we know very little about the number of species present, nor the evolutionary forces responsible for generating this diversity. One hypothesis is that trait diversity in the gall wasps, including the morphology of the galls they induce, has evolved in response to selection imposed by the parasitoid community, with reciprocal selection driving diversification of the parasitoids. Using a rare, continental‐scale data set of Sycophila parasitoid wasps reared from 44 species of cynipid galls from 18 species of oak across the USA, we combined mitochondrial DNA barcodes, ultraconserved elements (UCEs), morphological and natural history data to delimit putative species. Using these results, we generate the first large‐scale assessment of ecological specialization and host association in this species‐rich group, with implications for evolutionary ecology and biocontrol. We find most Sycophila target specific subsets of available cynipid host galls with similar morphologies, and generally attack larger galls. Our results suggest that parasitoid wasps such as Sycophila have adaptations allowing them to exploit particular host trait combinations, while hosts with contrasting traits are resistant to attack. These findings support the tritrophic niche concept for the structuring of plant–herbivore–parasitoid communities.

Investigating small unoccupied aerial systems (sUAS) multispectral imagery for total suspended solids and turbidity monitoring in small streams - Elizabeth M. Prior; Frances C. O’Donnell; Christian Brodbeck; G. Brett Runion; Stephanie L. Shepherd (International Journal of Remote Sensing, 2021)

Rethinking the interplay between affluence and vulnerability to aid climate change adaptive capacity - Christine Eriksen; Gregory L. Simon; Florian Roth; Shefali Juneja Lakhina; Ben Wisner; Carolina Adler; Frank Thomalla; Anna Scolobig; Kate Brady; Michael Bründl; Florian Neisser; Maree Grenfell; et al. (Climatic Change, 2020)
Affluence and vulnerability are often seen as opposite sides of a coin—with affluence generally understood as reducing forms of vulnerability through increased resilience and adaptive capacity. However, in the context of climate change and an increase in associated hazards and disasters, we suggest the need to re-examine this dynamic relationship—a complex association we define here as the Affluence–Vulnerability Interface (AVI). We review research in different national contexts to show how a more nuanced understanding of the AVI can (a) problematize the notion that increasing material affluence necessarily has a mitigating influence on social vulnerability, (b) extend our analysis of social vulnerability beyond low-income regions to include affluent contexts and (c) improve our understanding of how psychosocial characteristics influence people’s vulnerability. Finally, we briefly outline three methodological approaches that we believe will assist future engagement with the AVI.

Complete sequencing of the SMN2 gene in SMA patients detects SMN gene deletion junctions and variants in SMN2 that modify the SMA phenotype - Corey Ruhno; Vicki L. McGovern; Matthew R. Avenarius; Pamela J. Snyder; Thomas W. Prior; Flavia C. Nery; Abdurrahman Muhtaseb; Jennifer S. Roggenbuck; John T. Kissel; Valeria A. Sansone; Jennifer J. Siranosian; Alec J. Johnstone; et al. (Human Genetics, 2019)

Sex steroid profiles and pair-maintenance behavior of captive wild-caught zebra finches (Taeniopygia guttata) - Nora H. Prior; Kang Nian Yap; Hans H. Adomat; Mark C. Mainwaring; H. Bobby Fokidis; Emma S. Guns; Katherine L. Buchanan; Simon C. Griffith; Kiran K. Soma (Journal of Comparative Physiology A, 2016)

Insights from community ecology into the role of enemy release in causing invasion success: the importance of native enemy effects - Kirsten M. Prior; Thomas H. Q. Powell; Ashley L. Joseph; Jessica J. Hellmann (Biological Invasions, 2015)

Influence of aboveground tree biomass, home age, and yard maintenance on soil carbon levels in residential yards - Ann Huyler; Arthur H. Chappelka; Stephen A. Prior; Greg L. Somers (Urban Ecosystems, 2014)

Drivers of soil carbon in residential ‘pure lawns’ in Auburn, Alabama - Ann Huyler; Arthur H. Chappelka; Stephen A. Prior; Greg L. Somers (Urban Ecosystems, 2014)

Abrupt fire regime change may cause landscape‐wide loss of mature obligate seeder forests - David M. J. S. Bowman; Brett P. Murphy; Dominic L. J. Neyland; Grant J. Williamson; Lynda D. Prior (Global Change Biology, 2014)
Obligate seeder trees requiring high‐severity fires to regenerate may be vulnerable to population collapse if fire frequency increases abruptly. We tested this proposition using a long‐lived obligate seeding forest tree, alpine ash ( Eucalyptus delegatensis ), in the Australian Alps. Since 2002, 85% of the Alps bioregion has been burnt by several very large fires, tracking the regional trend of more frequent extreme fire weather. High‐severity fires removed 25% of aboveground tree biomass, and switched fuel arrays from low loads of herbaceous and litter fuels to high loads of flammable shrubs and juvenile trees, priming regenerating stands for subsequent fires. Single high‐severity fires caused adult mortality and triggered mass regeneration, but a second fire in quick succession killed 97% of the regenerating alpine ash. Our results indicate that without interventions to reduce fire severity, interactions between flammability of regenerating stands and increased extreme fire weather will eliminate much of the remaining mature alpine ash forest.

Land clearance not dieback continues to drive tree loss in a Tasmanian rural landscape - Lynda D. Prior; Gregor J. Sanders; Kerry L. Bridle; Scott C. Nichols; Rowan Harris; David M. J. S. Bowman (Regional Environmental Change, 2013)

Development of a specific molecular tool for the detection of epidemiologically active mulberry causing-disease strains of Ralstonia solanacearum phylotype I (historically race 5-biovar 5) in China - Z. C. Pan; J. Xu; P. Prior; J. S. Xu; H. Zhang; K. Y. Chen; Q. Tian; L. Q. Zhang; L. Liu; L. Y. He; J. Feng (European Journal of Plant Pathology, 2013)

Maximal oxygen consumption is best predicted by measures of cardiac size rather than function in healthy adults - André La Gerche; Andrew T. Burns; Andrew J. Taylor; Andrew I. MacIsaac; Hein Heidbüchel; David L. Prior (European Journal of Applied Physiology, 2012)

Diazepam Fluorimetric Monitoring Upon Photo-Degradation in an Automatic Miniaturized Flow System - David S. M. Ribeiro; João A. V. Prior; João L. M. Santos; José L. F. C. Lima (Journal of Fluorescence, 2010)

Genetic diversity of Ralstonia solanacearum strains from China - J. Xu; Z. C. Pan; P. Prior; J. S. Xu; Z. Zhang; H. Zhang; L. Q. Zhang; L. Y. He; J. Feng (European Journal of Plant Pathology, 2009)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Mutation update of spinal muscular atrophy in Spain: molecular characterization of 745 unrelated patients and identification of four novel mutations in the SMN1 gene - Laura Alías; Sara Bernal; Pablo Fuentes-Prior; María Jesus Barceló; Eva Also; Rebeca Martínez-Hernández; Francisco J. Rodríguez-Alvarez; Yolanda Martín; Elena Aller; Elena Grau; Ana Peciña; Guillermo Antiñolo; et al. (Human Genetics, 2009)

Do feral buffalo ( Bubalus bubalis ) explain the increase of woody cover in savannas of Kakadu National Park, Australia? - D. M. J. S. Bowman; J. E. Riley; G. S. Boggs; C. E. R. Lehmann; L. D. Prior (Journal of Biogeography, 2008)
Aim To study changes in woody vegetation in both floodplains and eucalypt savanna over a 40‐year period using multi‐temporal spatial analysis of variation in density of a large introduced herbivore, the Asian water buffalo ( Bubalus bubalis ). Feral buffalo built up to high densities in the study area until c. 1985, after which a control programme almost eliminated the animals. From 1990, low densities of managed buffalo were maintained inside an enclosure. We compared trends in woody vegetation when buffalo were high‐density feral, low‐density managed or absent. Location The study area was located in and around a 116‐km 2 buffalo enclosure inside Kakadu National Park, in monsoonal northern Australia. Methods We analysed sequences of digitized and geo‐rectified aerial photographs, acquired in 1964, 1975, 1984, 1991 and 2004, to chart changes in woody cover on the floodplain and in the savanna. On the floodplain we assessed whether trees were present at these times at 14,568 points, and buffalo density was estimated from the density of animal tracks. In the savanna we estimated woody cover at pre‐selected sites. Generalized linear modelling was used to analyse changes in woody vegetation, using elevation and presence of woody vegetation in neighbouring points on the floodplain, and buffalo regime and initial woody cover in the savanna . Results Changes in animal track density reflected park‐wide historical estimates of buffalo numbers. Tree cover increased in both floodplain and savanna, but this was only weakly related to buffalo density. The best predictor of whether a floodplain cell converted from treeless to woody, or the converse, was the woodiness of neighbouring vegetation. There was slightly less thickening with high buffalo densities. In savanna, low densities of managed buffalo were weakly associated with increases in tree cover relative to either high densities of feral buffalo or no buffalo. Main conclusions Our study indicates that buffalo are not a major driver of floodplain and eucalypt savanna dynamics. Rather, the observed increase in woody cover in both savanna and flood plains concords with regional trends and may be related to increased atmospheric CO 2 , increasing rainfall and changing fire regimes during the study period.

The response of two butterfly species to climatic variation at the edge of their range and the implications for poleward range shifts - Jessica J. Hellmann; Shannon L. Pelini; Kirsten M. Prior; Jason D. K. Dzurisin (Oecologia, 2008)

Accurate Determination of Zygosity in Transgenic Rice by Real-time PCR Does Not Require Standard Curves or Efficiency Correction - Fiona A. Prior; Eilleen S. Tackaberry; Rémy A. Aubin; William L. Casley (Transgenic Research, 2006)

Functional magnetic resonance imaging studies of opioid receptor-mediated modulation of noxious-evoked BOLD contrast in rats - Y. B. Shah; L. Haynes; M. J. W. Prior; C. A. Marsden; P. G. Morris; V. Chapman (Psychopharmacology, 2005)

Decomposition of soybean grown under elevated concentrations of CO 2 and O 3 - Fitzgerald L. Booker; Stephen A. Prior; H. Allen Torbert; Edwin L. Fiscus; Walter A. Pursley; Shuijin Hu (Global Change Biology, 2005)
A critical global climate change issue is how increasing concentrations of atmospheric CO 2 and ground‐level O 3 will affect agricultural productivity. This includes effects on decomposition of residues left in the field and availability of mineral nutrients to subsequent crops. To address questions about decomposition processes, a 2‐year experiment was conducted to determine the chemistry and decomposition rate of aboveground residues of soybean ( Glycine max (L.) Merr.) grown under reciprocal combinations of low and high concentrations of CO 2 and O 3 in open‐top field chambers. The CO 2 treatments were ambient (370 μmol mol −1 ) and elevated (714 μmol mol −1 ) levels (daytime 12 h averages). Ozone treatments were charcoal‐filtered air (21 nmol mol −1 ) and nonfiltered air plus 1.5 times ambient O 3 (74 nmol mol −1 ) 12 h day −1 . Elevated CO 2 increased aboveground postharvest residue production by 28–56% while elevated O 3 suppressed it by 15–46%. In combination, inhibitory effects of added O 3 on biomass production were largely negated by elevated CO 2 . Plant residue chemistry was generally unaffected by elevated CO 2 , except for an increase in leaf residue lignin concentration. Leaf residues from the elevated O 3 treatments had lower concentrations of nonstructural carbohydrates, but higher N, fiber, and lignin levels. Chemical composition of petiole, stem, and pod husk residues was only marginally affected by the elevated gas treatments. Treatment effects on plant biomass production, however, influenced the content of chemical constituents on an areal basis. Elevated CO 2 increased the mass per square meter of nonstructural carbohydrates, phenolics, N, cellulose, and lignin by 24–46%. Elevated O 3 decreased the mass per square meter of these constituents by 30–48%, while elevated CO 2 largely ameliorated the added O 3 effect. Carbon mineralization rates of component residues from the elevated gas treatments were not significantly different from the control. However, N immobilization increased in soils containing petiole and stem residues from the elevated CO 2 , O 3 , and combined gas treatments. Mass loss of decomposing leaf residue from the added O 3 and combined gas treatments was 48% less than the control treatment after 20 weeks, while differences in decomposition of petiole, stem, and husk residues among treatments were minor. Decreased decomposition of leaf residues was correlated with lower starch and higher lignin levels. However, leaf residues only comprised about 20% of the total residue biomass assayed so treatment effects on mass loss of total aboveground residues were relatively small. The primary influence of elevated atmospheric CO 2 and O 3 concentrations on decomposition processes is apt to arise from effects on residue mass input, which is increased by elevated CO 2 and suppressed by O 3 .

Palaeoenvironment and human impact in modifying vegetation at Mt St John, Auckland Isthmus, New Zealand - M. Horrocks; S. L. Nichol; D. M. D'Costa; P. Shane; C. Prior (New Zealand Journal of Botany, 2005)
A 2.34 m sediment profile from the base of the crater of Mt St John volcano (a small basaltic cone on Auckland Isthmus) provides a partial environmental record of the Late Quaternary. The record highlights potential age control problems with sediment cores taken directly from archaeological sites. Two distal tephras were recorded: 9.5 ka Rotoma and 7 ka Tuhua. A date of 16 309 ± 90 14C yr BP from the basal scoria of the profile provides a minimum date for the eruption of Mt St John. Pollen was present only in the upper 0.33 m of the profile, in a layer of peat and soil which caps highly weathered silts and clays eroded from the crater walls. In early Polynesian times (most likely after c. 800 14C yr BP), vegetation of the crater swamp was dominated by Cyperaceae sedges and Paesia ground fern. Dacrycarpus trees were also present. Podocarp‐hardwood forest, dominated by Metrosideros , grew on the rim and inner slopes of the crater. Elaeocarpus, Griselinia , and Cyathea were also present. A decline in Dacrycarpus pollen and an accelerated erosion rate mark Polynesian forest clearance within the crater. Typha became a major component of the swamp vegetation during the Late Polynesian‐European era.

Impact of Aboriginal landscape burning on woody vegetation in Eucalyptus tetrodonta savanna in Arnhem Land, northern Australia - D. M. J. S. Bowman; L. D. Prior (Journal of Biogeography, 2004)
Aim To compare woody vegetation of Eucalyptus tetrodonta savanna in an area that has had near continuous management by Aboriginal people with that of an area managed by neither Aborigines nor Europeans for the last 50 years. In particular, we tested the hypothesis that Aboriginal landscape burning increases the abundance of tree species, particularly those that bear edible fruit. We also examined whether Aboriginal burning increases tree density of the mid‐layer using measurements of the density and size distribution of all trees. Location Central Arnhem Land, a stronghold of traditional Aboriginal culture, in the Australian monsoon tropics. Methods Previous remote sensing analyses have shown that over the decade prior to field sampling, fires in the unmanaged area had produced a coarse‐scale mosaic of patches burnt between one to three times, in contrast the area under Aboriginal management was characterized by very high spatial and temporal variability of fire activity. In the study reported here, we assessed density, size distribution and taxonomic identity of trees in 78 and 79 plots (each 79–1385 m 2 in area) in the managed and unmanaged areas, respectively. Habitat attributes such as cover of rocks and bare ground and cover of various life forms were visually assessed for each plot, and density of grass and leaf litter was measured. Results Despite the contrasting fire regimes there were only minor differences in the fine fuels between the two areas, both of which had a low biomass of grass (dry weight was 35–221 g m −2 ). The composition and overall density of woody species was similar in the two areas but densities of fruit tree species and eucalypts were significantly higher, particularly in middle of the size class distribution of stems, in the unmanaged area while a few species, such as the fire sensitive conifer Callitris intratropica , were more abundant in the managed area. Main conclusions Our findings suggest that current Aboriginal landscape burning has a significant impact on vegetation structure, specifically stems in the middle of the size class distribution, but little effect on either species composition or total tree density. Such burning reduced the abundance of fruit bearing trees but had little effect on grass or fine fuel biomass. The vegetation structure in the area managed by Aborigines was similar to that reported for many savannas subjected to European fire regimes; a core difference, however, was lower biomass of tall grasses and greater abundance of C. intratropica . These data provide important empirical corroboration of previous descriptive ethnographic and historical analyses that vegetation structure at the time of settlement was strongly influenced by indigenous peoples’ use of fire. Thus our results not only inform contemporary land management but also provide insights into the role humans played in the evolution of Australia's remarkably flammable flora. Given our inability to use a replicated experimental design the generality of these conclusions require testing by comparing the findings of allied studies conducted elsewhere in northern Australia.

Landscape analysis of Aboriginal fire management in Central Arnhem Land, north Australia - D. M. J. S. Bowman; Angie Walsh; L. D. Prior (Journal of Biogeography, 2004)
Aim To describe the spatial and temporal pattern of landscape burning with increasing distance from Aboriginal settlements. Location Central Arnhem Land, a stronghold of traditional Aboriginal culture, in the Australian monsoon tropics. Methods Geographical information system and global positioning system technologies were used to measure spatial and temporal changes in fire patterns over a one decade period in a 100 × 80 km area that included a cluster of Aboriginal settlements and a large uninhabited area. The major vegetation types were mapped and fire activity was assessed by systematic visual interpretation of sequences of cloud‐free Landsat satellite images acquired in the first (May to July) and second (August to October) halves of the 7‐month dry season. Fire activity in the middle and end of one dry season near an Aboriginal settlement was mapped along a 90‐km field traverse. Canopy scorch height was determined by sampling burnt areas beside vehicle tracks. Results Satellite fire mapping was 90% accurate if the satellite pass followed shortly after a fire event, but the reliability decayed dramatically with increasing time since the fire. Thus the satellite mapping provided a conservative index of fire activity that was unable to provide reliable estimates of the spatial extent of individual fires. There was little landscape fire activity in the first half of the dry season, that was mostly restricted to areas immediately surrounding Aboriginal settlements, with burning of both inhabited and uninhabited landscapes concentrated in the second half of the dry season. The mean decadal fire indices for the three dominant vegetation types in the study area were three in the plateau savanna, two in the sandstone and five in the wet savanna. The spatial and temporal variability of Aboriginal burning apparent in the satellite analyses were verified by field traverse surrounding a single settlement. Fires set by Aborigines had low scorch height of tree crowns reflecting low intensity, despite generally occurring late in the dry season. Conclusions Our findings support the idea that Aboriginal burning created a fine‐scale mosaic of burnt and unburnt areas but do not support the widely held view that Aboriginal burning was focused primarily in the first half of the dry season (before July). The frequency and scale of burning by Aborigines appears to be lower compared with European fire regimes characterized by fires of annual or biennial frequencies that burn large areas. The European fire regime appears to have triggered a positive feedback cycle between fire frequency and flammable grass fuels. The widely advocated management objective of burning in the first half of the dry season burning provides one of the few options to control fires once heavy grass fuel loads have become established, however we suggest it is erroneous to characterize such a regime as reflecting traditional Aboriginal burning practices. The preservation of Aboriginal fire management regimes should be a high management priority given the difficulty in breaking the grass‐fire cycle once it has been initiated.

Population Genetic Structure in the Black Rat Snake: Implications for Management - K. A. Prior; H. L. Gibbs; P. J. Weatherhead (Conservation Biology, 1997)
Assessments of population genetic structure and diversity can be of value in formulating management plans for threatened species. Using randomly amplified polymorphic DNA markers, we found evidence of significant genetic structure among black rat snakes ( Elaphe obsoleta) sampled at three spatial scales. Highly isolated (1500–1900 km apart) populations were strongly divergent ( F ST = 0.242–0.323), whereas populations more proximal ( 465 km apart) although currently isolated, exhibited far less divergence ( F ST = 0.019). A considerable proportion (80%) of total genetic diversity was due to differences among individuals within populations, although differences among populations (8%) also were significant. At the scale of sub‐populations ( local populations 15–50 km apart), differentiation was generally moderate ( F ST = 0.058). Our estimates of Nei’s genetic distance for sub‐populations (0.014) approximated (mean = 0.044) those obtained in other studies that have assessed differentiation between snake populations based on variation in allozymes. The majority (ca. 86%) of total genetic variance across five sub‐populations was attributable to differences among individuals, although differences among sub‐populations (ca. 13%) also were significant. We found little evidence of genetic structure ( F ST = 0.006) between pairs of hibernacula, our finest spatial scale (samples 1–2 km apart), if they were located in natural habitats. In contrast, a pair of hibernacula sampled in an urban area exhibited genetic structure equivalent to some sub‐population differences ( F ST = 0.039), suggesting interrupted gene flow related to urban development. Our results have direct implications for ranking populations in terms of their conservation value and the genetic management of threatened snakes.